Harnessing Multiple, Nonproteogenic Substitutions to Optimize CSP:ComD Hydrophobic Interactions in Group 1 Streptococcus pneumoniae. (7th April 2021) - Milly, Tahmina A.; Engler, Emilee R.; Chichura, Kylie S.; Buttner, Alec R.; Koirala, Bimal; Tal‐Gan, Yftah; Bertucci, Michael A.
Abstract: Streptococcus pneumoniae (pneumococcus) is a human pathobiont that causes drastic antibiotic‐resistant infections and is responsible for millions of deaths universally. Pneumococcus pathogenicity relies on the competence‐stimulating peptide (CSP)‐mediated quorum‐sensing (QS) pathway that controls competence development for genetic transformation and, consequently, the spread of antibiotic resistance and virulence genes. Modulation of QS in S. pneumoniae can therefore be used to enervate pneumococcal infectivity as well as minimize the susceptibility to resistance development. In this work, we sought to optimize the interaction of CSP1 with its cognate transmembrane histidine kinase receptor (ComD1) through substitution of proteogenic and nonproteogenic amino acids on the hydrophobic binding face of CSP1. The findings from this study not only provided additional structure–activity data that are significant in optimizing CSP1 potency, but also led to the development of potent QS modulators. These CSP‐based QS modulators could be used as privileged scaffolds for the development of antimicrobial agents against pneumococcal infections. Abstract : Unnaturally optimized : The use of unnatural amino acids allowed the optimization of hydrophobic interactions between CSP1 and the cognate ComD1 receptor by assessing how multiple, coordinated substitutions in the CSP1 amino acid sequence can affect CSP1 binding.